The house on Prytania [large type] - White, Karen (Karen S.) (White, Karen (Karen S.). Royal Street novel., 2023)
"Nola Trenholm may not be psychic herself, but she's spent enough time around people who are to know when ghosts are present, and there are definitely a few lingering spirits in her recently purchased Creole cottage in New Orleans. Something, or someone, is keeping them tethered to this world. And not all of them are benign. But with the sudden return of Sunny Ryan, Beau Ryan's long-lost sister, Nola has plenty to distract her from her ghostly housemates. Especially when the tempting--yet firmly unavailable--Beau, wanting to mete out justice to those he blames for Sunny's kidnapping, asks Nola for a favor that threatens to derail her hard-won recovery and send her hurtling backward"--